Particularidades fonéticas del quechua Yaru-Huánuco - Dominguez Condezo, Víctor (2006)
After establishing the relativity of authentic Kechwa, this essay describes the varieties of the Yaru-Huanuco kechwa supralect and the phonetic characteristics spoken in Huamalíes, Dos de Mayo, Valle del Pillko, Panao, Pampa de Junín, Chaupiwaranga and Cerro de Pasco, based on texts collected and tape recorded on site, in the above mentioned sociolectal areas. We present the degree of understanding of radio broadcasted programmes of seven Peruvian supralects, analysed by Alfredo Torero and, based on this model, we try to point out the sociolectal differences of Kechwa in Ancash-Huaylas and Yaru-Huanuco (Quechua I, studied by our friend and most important Linguist). Finally we note down the very special phonetic differences of sounds: [ch], [tr], [ts] y [s].